2005
DOI: 10.1080/03610730590948186
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of Spaced-Retrieval Memory Training for Older Adults with Probable Alzheimer's Disease

Abstract: Ten older adults with probable Alzheimer's disease (AD) were trained to recall everyday objects using the spaced-retrieval technique. Five persons had participated in a prior spaced-retrieval program (Cherry & Simmons-D'Gerolamo, 1999, Clinical Gerontologist, 20, 39-63). The authors retested these original participants to measure the long-term effectiveness of spaced-retrieval training. Five new participants were included for comparison purposes. During training, participants selected a target object from an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
2
25
0
2
Order By: Relevance
“…To our knowledge, our results are the first to show retention of an association that includes social information about the target person (i.e., name, face, and occupation). Our findings are also compatible with prior research in which spaced retrieval effects were found using common household objects as the training material (Cherry & Simmons-D'Gerolamo, 2004, 2005.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, our results are the first to show retention of an association that includes social information about the target person (i.e., name, face, and occupation). Our findings are also compatible with prior research in which spaced retrieval effects were found using common household objects as the training material (Cherry & Simmons-D'Gerolamo, 2004, 2005.…”
Section: Discussionsupporting
confidence: 94%
“…Spaced retrieval training gains have been demonstrated across different types of materials (common household objects, Cherry & Simmons-D'Gerolamo, 1999, 2004, 2005 names of caregivers, Camp & Schaller, 1989; face-name associations, Hawley & Cherry, 2004;Joltin, Camp, & McMahon, 2003). Long-term maintenance of the trained material has also been found (Cherry & Simmons-D'Gerolamo, 2005;Clare, Wilson, Carter, Hodges, & Adams, 2001), suggesting that the technique may be well suited for addressing real-world memory tasks in which retention is often required long after initial acquisition. Hawley and Cherry (2004) trained six older adults with probable AD to remember an unfamiliar name-face association using spaced retrieval.…”
mentioning
confidence: 93%
“…In this form, the intervals were adjusted according to the patient's performance. Several studies have demonstrated that adjusted SRT is efficacious in individuals with probable AD and leads to an improvement in associative memory (Hawley and Cherry, 2004;Cherry and Simmons-D'Gerolamo, 2005;Hopper et al, 2005Hopper et al, , 2010Hawley et al, 2008;Cherry et al, 2010).…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…As carers' coping capacity is linked to placement of people with dementia into residential care (Brodaty, Gresham, & Luscombe, 1997), removing sources of frustration by supporting everyday function through spaced retrieval training could, potentially, delay placement. The effects of longer-term support of everyday function through spaced retrieval training (as also reported by Cherry & Simmons-D'Gerolamo, 2005) warrant further investigation especially in conjunction with more emphasis on the effects of successful training on family carers and their quality of life (Hawley & Cherry, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…and colleagues (Cherry & Simmons-D'Gerolamo, 2005;Cherry, Hawley, Jackson & Boudreaux, 2009) have also shown that researcher-nominated training goals achieved through spaced retrieval training can be maintained for 6 to 9 months. Demonstrating that participant-nominated training goals can be maintained could further strengthen the practical utility of spaced retrieval training, especially if individuals were able to use trained information to support day-to-day activities.…”
mentioning
confidence: 90%